Study on Morphology, Thermal and Physical Properties of Poly(trimethylene terephthalate)-Nano Silica Composite - MALEKNIA, LALEH; NAZOCKDAST, HOSSEIN; ARASTEH, ROHOALLAH; HEMMATI, MAHMOOD; YOUSEFI, KIA (Asian Journal of Chemistry, 2010)
The morphology, thermal behaviour and melt viscoelastic properties of polytrimethylene terephthalate-nano silica containing 2, 4 and 8 % of nano silica were investigated. The blend samples were prepared by an internal mixer. The results obtain from DSC showed that the heat of crystallization (ΔHcry) of poly(trimethylene terephthalate) matrix follows a decreasing trend with increasing the nano particle up to 8 % above which it begins to increase again. The decrease in ΔHcry of the poly- (trimethylene terephthalate) can be related to strong interaction between PTT and nano particle surface. The crystallization temperatures (Tc) of the poly(trimethylene terephthalate) matrix increase with the increasing nano particle concentration but it decrease with increase 8 % of nano silica. Cryogenically fractured surface of the samples examined by SEM. The results obtain from SEM showed the samples containing 8 % of nano particle showed a great extent of agglomeration formed between the nano particles. The melt flow behaviour and viscoelastic properties were studied by using a rheometre mechanical spectrometer (RMS). The results obtain from RMS showed viscoelastic properties for poly(trimethylene terephthalate) and the samples containing 2 and 4 % of nano particle are almost similar while the sample containing 8 % of nano particle exhibits a pronounced viscosity upturn with high and nonterminal storage modulus at low frequency range.